Faktor–Faktor Penyebab Rendahnya Minat Siswa Terhadap Pembelajaran Seni Tari Di SMP Negeri 1 Payakumbuh - Ines Hardi; Yuliasma Yuliasma; Darmawati Darmawati (SENDRATASIK UNP, 2019)
This article aimed to find out and describe the factors that caused students' low interest in the process of learning dance at SMPN 1 Payakumbuh. The type of this research was qualitative research using descriptive methods. The main instrument of research was the researcher herself and assisted with supporting instruments such as stationeries and camera. The types of data were primary and secondary data. Thetechniques of data collectionwere done by library research, direct observation in the field, interviews and documentation. The data were analyzed through these steps, namely 1) data reduction, 2) data presentation and 3) data verification or data inference. The results of the study showed that the factors that caused students' low interest in learning dance were internal (from students) and external (from the teacher) factors. Internal factors were seen from 2 indicators, namely desire and discipline. The results of observations from meetings 1 to 4 showed that many students did not respond to the questions asked by the teacher. It was also supported by interview data, they did not like the learning of dance because it needed a lot of time to practice. Meanwhile, external factors included teachers, methods, media, teacher attitudes, and infrastructures. Teacher's external factors included the attitude, method and the media.The teacher's attitude that was less assertive influencing many students to behave indifferently in learning, such as making noise, disturbing friends, so that the class became less conducive. The use of various methods had not been able to help achieving the learning goals. This could be observed in the low interest to learn. Each teacher asked questions, but studentsanswered them rarely. The media used had not supported students to absorb the knowledge and skills. Factors of facilities had not supported learning activities. Thus the factors causing students’ low interest in learning dance were internal factors and external factors.